Tumor MHC class I expression alters cancer-associated myelopoiesis driven by host NK cells - Juan Gao; Andreas Lundqvist; Xu Jing; Yihai Cao; Le Tong; Shi Yong Neo; Dongmei Tong; Ziqing Chen; Mireia Cruz De Los Santos; Nutsa Burduli; Sabrina De Souza Ferreira; Arnika Kathleen Wagner; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Downregulation of MHC class I (MHCI) molecules on tumor cells is recognized as a resistance mechanism of cancer immunotherapy. Given that MHCI molecules are potent regulators of immune responses, we postulated that the expression of MHCI by tumor cells influences systemic immune responses. Accordingly, mice-bearing MHCI-deficient tumor cells showed reduced tumor-associated extramedullary myelopoiesis in the spleen. Depletion of natural killer (NK) cells abrogated these differences, suggesting an integral role of immune-regulatory NK cells during tumor progression. Cytokine-profiling revealed an upregulation of TNF-α by NK cells in tumors and spleen in mice-bearing MHCI expressing tumors, and inhibition of TNF-α enhanced host myelopoiesis in mice receiving adoptive transfer of tumor-experienced NK cells. Our study highlights a critical role of NK cells beyond its identity as a killer lymphocyte and more importantly, the potential host responses to a localized tumor as determined by its MHCI expression.